2017
DOI: 10.1002/lary.26473
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thyroid cancer incidence, post‐2009 American Thyroid Association guidelines

Abstract: 2c. Laryngoscope, 127:2437-2441, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
1
31
0
3
Order By: Relevance
“…It has been reported that overall thyroid cancer incidence had an increasing trend about 8% per year from 2000 to 2009. But APC showed a deceleration about 3% in men and 2.8% in women, which was conined to tumors less than 2.9 cm of size for women [7].…”
Section: Detailed Epidemiology Of Thyroid Cancermentioning
confidence: 91%
See 2 more Smart Citations
“…It has been reported that overall thyroid cancer incidence had an increasing trend about 8% per year from 2000 to 2009. But APC showed a deceleration about 3% in men and 2.8% in women, which was conined to tumors less than 2.9 cm of size for women [7].…”
Section: Detailed Epidemiology Of Thyroid Cancermentioning
confidence: 91%
“…A recently published study on adolescent cancer incidence during 1975-2012 has reported a 2.12% increase for females and 1.59% for males between 15 and 19 years of age [5]. However, there is a study indicating that thyroid cancer incidence trend has slowed following release of American Thyroid Association (ATA) guideline in 2009 [6,7]. It has been reported that overall thyroid cancer incidence had an increasing trend about 8% per year from 2000 to 2009.…”
Section: Detailed Epidemiology Of Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Over a 15‐year period (1995–2009), a 94% increase in the procedure was reported. The trend continues unabated, in keeping with the growing incidence of thyroid cancer over the last three decades …”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, the incidence rate for differentiated thyroid carcinomas in the United States is approximately 20 per 100,000 females and 6 per 100,000 males, predominantly papillary and follicular carcinoma. 5 Similarly, negative resection margins are the primary prevention of disease recurrence for thyroid cancer. 6 This study aims to investigate the ability of HSI using convolutional neural networks to classify tissue at the cancer margin.…”
Section: Introductionmentioning
confidence: 99%